Metaphoric Architecture in Painan Maritime Museum Design - Fardinan, Rolly; Fuadi, Al Busyra; Triana, Era; Haryani, Haryani; Mulfakli, Mulfakli; Kusumah, Dadang Puja (SIGMA TEKNIKA, 2025)
Metaphorical architecture translates cultural and natural phenomena into readable spatial narratives. This article develops a framework of five variables—source metaphor, key attributes, domain transfer, spatial narrative, and symbolic legibility—synthesized from comparative precedent studies (Libeskind’s Jewish Museum Berlin and the Aceh Tsunami Museum) and applies it to the design of the Painan Maritime Museum in West Sumatra. Local sources such as the traditional pincalang boat, Indian Ocean waves, and communal fishing activities are transformed into a ship-oriented elongated mass, undulating façade, net-patterned secondary skin, and sequential linear circulation forming a symbolic “voyage”: embarkation, tension, climax, reflection, and epilogue. The analysis reveals a balance between iconic legibility and conceptual depth, enabling visitors to intuitively perceive local maritime identity. This study contributes to the development of a transferable design methodology for metaphor-based museums and provides contextual site recommendations for the coastal landscape of Carocok Beach, Painan.